Impacto das campanhas de vacinação contra influenza sobre a morbimortalidade por doenças respiratórias em idosos na região metropolitana de Belém - GUEDES, João Daniel Cardoso (2022)
This ecological study aimed to evaluate the effect of annual revaccination against influenza in elderly persons on trends of mortality rates and hospitalization rates for respiratory diseases from 1990 to 2006 for mortality and from 1992 to 2006 for hospitalizations. Mortality rates for respiratory diseases increased during the period studied. However, when it analyzed separately this trend of mortality from pneumonia and influenza, there was decreased of mortality rates by 1996 to reverse trend with acceleration. About hospitalization rates, it was found to decrease after vaccine intervention, except the group above 80 years of age. Evaluating only hospitalizations for pneumonia and influenza, hospitalization rates were increased during the period and more pronounced in males and those older than 80 years. The analysis of the monthly rates showed seasonal behavior with a small-scale peak between months March to May and constant pattern in rest of the year. Among the hypotheses to explain these findings are inequalities in vaccination coverage into elderly population, vaccination campaign in period not optimum of the year, low correlation between vaccine strains and predominant circulating strains of influenza virus and circulation other pathogens related to flu-like syndromes.